Revisiting the African supermarket revolution: The case of Windhoek, Namibia. Issue 2 (4th March 2021) - Nickanor, Ndeyapo; Kazembe, Lawrence N.; Crush, Jonathan; Wagner, Jeremy
ABSTRACT: Africa is rapidly urbanising and urban food systems are being transformed. Some have argued that this transformation is driven by a supermarket revolution akin to that in North America, Europe and Latin America. Others suggest that the supermarket revolution model oversimplifies complex African realities and that urban food systems are experiencing uneven supermarket penetration in the face of resilient informal food sectors. This paper focuses on Windhoek, Namibia, showing that the city's food system is dominated by South African and local supermarket chains. Since the end of apartheid, South African supermarket chains have expanded their operations into Namibia. Supermarket domination of Windhoek's urban food system is a function of proximity of South Africa and integration into South African supply chains. In other African countries, supermarket penetration has been much slower and is even being reversed. Explanations for uneven penetration in different countries require greater contextualisation and more case study research.